The Impact of Tiktok Application Users in Social Life - Rokan, Nadira Zuhra; Monang, Sori (Pena Cendekia Insani, 2023)
Increasingly sophisticated technology never desires and even further encourages human curiosity. One of the influences of technology that cannot be separated from life is social media. When the COVID-19 pandemic occurred, the TikTok application was present in the midst of society to accompany people when people were forced to stay at home. Therefore, researchers want to find out how the influence of TikTok application users for the people of Pasar Merah Timur.